Preconditioning with far-infrared irradiation enhances proliferation, cell survival, and migration of rat bone marrow-derived stem cells via CXCR4-ERK pathways. Issue 1 (December 2017) - Jeong, Yun-Mi; Cheng, Xian; Lee, Sora; Lee, Kyung; Cho, Haneul; Kang, Jung; Kim, Weon
Abstract Far-infrared radiation (FIR) has been shown to exert positive effects on the cardiovascular system. However, the biological effects of FIR on bone marrow-derived stem cells (BMSCs) are not understood. In the present study, BMSCs were isolated from rat femur bone marrow and culturedin vitro . To investigate the effects of an FIR generator with an energy flux of 0.13 mW/cm2 on rat BMSCs, survival of BMSCs was measured by crystal violet staining, and cell proliferation was additionally measured using Ez-Cytox cell viability, EdU, and Brd U assays. FIR preconditioning was found to significantly increase BMSC proliferation and survival against H2 O2 . The scratch and transwell migration assays showed that FIR preconditioning resulted in an increase in BMSC migration. qRT-PCR and Western blot analyses demonstrated that FIR upregulated Nanog, Sox2, c-Kit, Nkx2.5, and CXCR4 at both the mRNA and protein levels. Consistent with these observations, PD98059 (an ERK inhibitor) and AMD3100 (a CXCR4 inhibitor) prevented the activation of CXCR4/ERK and blocked the cell proliferation and migration induced by FIR. Overall, these findings provide the first evidence that FIR confers a real and significant benefit on the preconditioning of BMSCs, and might lead to novel strategies for improving BMSC therapy for cardiac ischemia.